PERANCANGAN DAN PEMBUATAN ALAT PEMOTONG SERAT NANAS MENGGUNAKAN SISTEM PNEUMATIK - Eka Putra, Ismet; Hendra, Boy (Jurnal Teknologi dan Vokasi, 2023)
Making a tool that can help cut natural fiber composite raw materials (pineapple fiber) automatically, can increase efficiency and make it easier to cut, both in terms of speed, power, amount of production, to the safety factor of the cutting machine. The results of the test show that using a pneumatic system pineapple fiber cutting tool can cut fibers quickly to meet the need for pineapple fiber as a raw material for composite materials and also avoid situations where when cutting fibers manually you will feel tired because performance decreases and it greatly affects safety level that can be dangerous in the cutting process. The difference in pressure applied to the system varies by 2, 3, 4, 5 bar with varying cutting results, namely 61, 100, 113, and 150 cuts every 60 seconds. This pneumatic system pineapple fiber cutter is capable of cutting in 0.41 seconds with an air pressure of 5 bar.